If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(9c + -1) + -18 = 52c + 6 Reorder the terms: 6(-1 + 9c) + -18 = 52c + 6 (-1 * 6 + 9c * 6) + -18 = 52c + 6 (-6 + 54c) + -18 = 52c + 6 Reorder the terms: -6 + -18 + 54c = 52c + 6 Combine like terms: -6 + -18 = -24 -24 + 54c = 52c + 6 Reorder the terms: -24 + 54c = 6 + 52c Solving -24 + 54c = 6 + 52c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-52c' to each side of the equation. -24 + 54c + -52c = 6 + 52c + -52c Combine like terms: 54c + -52c = 2c -24 + 2c = 6 + 52c + -52c Combine like terms: 52c + -52c = 0 -24 + 2c = 6 + 0 -24 + 2c = 6 Add '24' to each side of the equation. -24 + 24 + 2c = 6 + 24 Combine like terms: -24 + 24 = 0 0 + 2c = 6 + 24 2c = 6 + 24 Combine like terms: 6 + 24 = 30 2c = 30 Divide each side by '2'. c = 15 Simplifying c = 15
| -36+p=1 | | x^2-14x+44=0 | | -2x+20=x+8 | | -x^2+12x+12=0 | | -2+20=x+8 | | -10(x+4)+52=-14-14 | | 4x-11=-2+22 | | x-5=2x+3 | | x^3-60x^2+11x-60=0 | | 4(5c-1)-3=16c+9 | | x^3+60x^2+11x-60=0 | | 64x^2-32x+3=0 | | 3w-2x=w-4 | | 3x+3=x+1 | | 2x^2-2x+x-1=2x^2-6x+3x-9 | | 3n+7=30 | | 3x^2-4x-4=0 | | (5b-3)-2(2b+2)=-5 | | 5x-(4x+4)=1 | | -x+13=x+5 | | x+13=x+5 | | -x^2+x-6=0 | | x^2+16x+62=0 | | (x-2)(x-4)=(x-3)(x+6) | | 64x^2+9=-48x | | 4y=8x-3 | | x^2+14x+46=0 | | (x+3)=7 | | x^2+30x=0 | | x^2+6x-55=0 | | (x-4)(x-4)=16 | | 4x^2=324 |